Constitutive expression of spliced X-box binding protein 1 inhibits dentin formation in mice - Xu, Qian; Li, Jiahe; Zhang, Hua; Wang, Suzhen; Qin, Chunlin; Lu, Yongbo (Frontiers in Physiology, 2024)
Upon endoplasmic reticulum (ER) stress, inositol-requiring enzyme 1 (IRE1) is activated, which subsequently converts an unspliced X-box binding protein 1 (XBP1U) mRNA to a spliced mRNA that encodes a potent XBP1S transcription factor. XBP1S is essential for reliving ER stress and secretory cell differentiation. We previously established Twist2-Cre;Xbp1CS/+ mice that constitutively expressed XBP1S in the Twist2-expressing cells as well as in the cells derived from the Twist2-expressing cells. In this study, we analyzed the dental phenotype of Twist2-Cre;Xbp1CS/+ mice. We first generated a mutant Xbp1s minigene that corresponds to the recombinant Xbp126 allele (the Xbp1CS allele that has undergone Cre-mediated recombination) and confirmed that the Xbp1s minigene expressed XBP1S that does not require IRE1α activation in vitro. Consistently, immunohistochemistry showed that XBP1S was constitutively expressed in the odontoblasts and other dental pulp cells in Twist2-Cre;Xbp1CS/+ mice. Plain X-ray radiography and µCT analysis revealed that constitutive expression of XBP1S altered the dental pulp chamber roof- and floor-dentin formation, resulting in a significant reduction in dentin/cementum formation in Twist2-Cre;Xbp1CS/+ mice, compared to age-matched Xbp1CS/+ control mice. However, there is no significant difference in the density of dentin/cementum between these two groups of mice. Histologically, persistent expression of XBP1S caused a morphological change in odontoblasts in Twist2-Cre;Xbp1CS/+ mice. Nevertheless, in situ hybridization and immunohistochemistry analyses showed that continuous expression of XBP1S had no apparent effects on the expression of the Dspp and Dmp1 genes. In conclusion, these results support that sustained production of XBP1S adversely affected odontoblast function and dentin formation.